Novel Regulatory Mechanisms of Pathogenicity and Virulence to Combat MDR in Candida albicans - Saif Hameed; Zeeshan Fatima (International Journal of Microbiology)
Continuous deployment of antifungals in treating infections caused by dimorphic opportunistic pathogen Candida albicans has led to the emergence of drug resistance resulting in cross-resistance to many unrelated drugs, a phenomenon termed multidrug resistance (MDR). Despite the current understanding of major factors which contribute to MDR mechanisms, there are many lines of evidence suggesting that it is a complex interplay of multiple factors which may be contributed by still unknown mechanisms. Coincidentally with the increased usage of antifungal drugs, the number of reports for antifungal drug resistance has also increased which further highlights the need for understanding novel molecular mechanisms which can be explored to combat MDR, namely, ROS, iron, hypoxia, lipids, morphogenesis, and transcriptional and signaling networks. Considering the worrying evolution of MDR and significance of C. albicans being the most prevalent human fungal pathogen, this review summarizes these new regulatory mechanisms which could be exploited to prevent MDR development in C. albicans as established from recent studies.